Harnessing Technology to Address the Global Mental Health Crisis - Batada, Amirali; Leon Solano, Rene (World Bank, Washington, DC, 2019)
The mounting challenges of global mental health are affecting millions of individuals throughout industrialized and developing regions of the world. One key factor hindering the progress of addressing mental illness lies in the structural imbalance between inadequate capacity to extend support, and the high growth rate of individuals requiring treatment. Addressing this gap in a timely and effective manner will warrant innovative approaches that operate in parallel with traditional strategies. This approach will assist in resolving the key challenges and barriers associated with the planning, design, and deployment of effective mental health services, and reducing the risk factors associated with mental illness. The application of emerging technologies holds promise in potentially addressing different dimensions of the global mental health challenge. This brief explores how select technologies and tools can potentially garner new insights, build efficiencies, and scale support in responding to the mental health challenges unfolding in a wide array of communities and contexts.